BOOK REVIEW: Cristina Jelescu, Radu Crutzescu, Ioan C. Filitti (eds.), "Amintirile colonelului Lăcusteanu”, Bucureşti: Humanitas, 2015 - RADU, Iazmina-Maria (Studia Universitatis Babeș-Bolyai Historia, 2019)
The subsequent years of the 1848 Revolution in Wallachia and Moldavia offered us a series of memoires and writings containing details about the significance of events during the revolutionary time. Many of them emphasized the positive impact of the Revolution and the main actors of it, but something was missing. The memoirs of Grigore Lăcusteanu emphasized the other part of the statement. In Transylvania we take benefit from John Page’s, who brings accusations to the Romanians revolutionaries, however he doesn’t convict the Revolution itself, considering he takes part of it next to the Hungarians. In Wallachia, starting with 1865 a manuscript, forbidden for a long time, builds a different atmosphere, from an anti-revolutionary point of view.